PERBANDINGAN PENGARUH OLAHRAGA ZUMBA DAN CARDIO DANCE TERHADAP PENURUNAN LEMAK TUBUH DAN BMI PADA MAHASISWA - Diana Putri Malta, - (2019)
Zumba and cardio dance are popular and worldwide sports among women nowadays. Zumba and cardio dance are forms of physical activity that can tighten the muscles in the body, maintain stamina, improve health and fitness, keeping to stay young, and improve blood circulation in the body. The purpose of this study is to examine whether there are differences in the effects of Zumba and cardio dance on decreasing body fat and BMI. This research method is quasi-experimental with Pre-test Post-test Control Group Design. The research sample consisted of 30 UPI Nursing students, consisting of 15 zumba groups and 15 cardio dance groups with sampling techniques using purposive sampling. Body fat measurement instruments using Skinfold Caliper and BMI measurements using the Omron Karada Scan scale. Data analysis using Paired Sample Ttest and Independent Sample Test. The results stated that there were significant effects of zumba and cardio dance on decreasing body fat and BMI, then there were no differences in the effect of zumba and cardio dance on decreasing body fat and BMI in students. Recommendations for further research are recommended to control food. Keywords: Zumba, cardio dance, body fat, BMI.